Development and validation of odour identification tests for olfactory assessment in Singapore - Xinni Xu; Margaret Ru Xiang Zhang; Terese Huiying Low; Yew Kwang Ong (Annals, Academy of Medicine, Singapore)
Introduction: Odour recognition is influenced by culture. Odour identification tests need to be adapted to a population to accurately assess olfactory function. This study’s objectives were to validate the Singapore version of the Sniffin’ Sticks (SS-Sg) and a locally-developed odour recognition test (Scentsor) for Singapore. Method: This prospective study was performed in 3 otolaryngology outpatient clinics in 3 phases (1 May to 15 November 2024). Phase 1 was a survey evaluation of 93 odour descriptors to identify familiar odour descriptors to be used in the tests (n=414); Phase 2 evaluated and finalised SS-Sg and Scentsor to ensure test odours were recognised by equal or more than 75% of healthy controls (n=130); and Phase 3 validated both tests on healthy controls (n=473) to obtain normative data, to determine test-retest reliability (n=50), and to assess the ability to distinguish patients with olfactory loss (n=67). Results: In Phase 1, the unmodified SS blue and purple sets had 15/32 (46.9%) unfamiliar test odours and 25 unfamiliar distractors combined. In Phase 2, after modification, all odours in SS-Sg and Scentsor were correctly identified by equal or more than 75% of controls. In Phase 3, normative data (age 21–83 years) was obtained. Both tests had good test-retest reliability (Pearson’s correlation coefficient of 0.88 with P < 0.001 for SS-Sg; and at 0.90 with P < 0.001 for Scentsor). Both tests differentiated among normosmia, hyposmia and anosmia (SS-Sg scores: 12.6 [plus minus 2.4] versus [vs] 9.8 (plus minus 3.2) vs 6.0 [plus minus 2.3] respectively, P < 0.001; Scentsor scores: 14.3 [plus minus 1.8] vs 11.3 [plus minus 2.8] v. 5.8 [plus minus 3.4] respectively, P < 0.001). Conclusion: SS-Sg and Scentsor have been validated to assess olfaction in Singapore.